Pengaruh Struktur Modal Dan Good Corporate Governance Terhadap Kinerja Keuangan Dengan Financial Distress Sebagai Variabel Intervening Pada Perusahaan Sub Sektor Food And Beverage Yang Terdaftar Di Bursa Efek Indonesia Periode 2020-2023 - Larasati, Devira; Riyadi, Slamet (Cattleya Darmaya Fortuna, 2025)
This research intends to prove and analyze the effect of Capital Structure and GCG on Financial Performance through Financial Distress as an intervening variable in food and beverage sub-sector companies listed on the IDX for the period 2020-2023. Companies in the food and beverage sub-sector listed on the IDX for the period 2020-2023 are the population of this research. The sample in this study amounted to 100 samples and was determined using purposive sampling technique. This research uses path analysis using SmartPLS 2.0 as the analysis technique. The findings of this research prove that Capital Structure has a significant effect on Financial Distress, GCG has a significant effect on Financial Distress, Capital Structure has an insignificant effect on Financial Performance, GCG has an insignificant effect on Financial Performance, Financial Distress has a significant effect on Financial Performance, Financial Distress plays a significant role as an intervening variable in the relationship between Capital Structure and Financial Performance, Financial Distress plays a significant role as an intervening variable in the relationship between GCG and Financial Performance.